DEVELOPMENT OF ZATASE (ZATHURA BERBASIS ASSEMBLR EDU) LEARNING MEDIA IN THE SCIENCE SUBJECT OF GRADE VI IN MADRASAH IBTIDAIYAH - Fadilla, Nur; Junaidi, Muhammad (Al-Aulad: Journal of Islamic Primary Education, 2025)
This study aims to determine the development, feasibility and effectiveness of ZATASE (Zathura based on Assemblr Edu) learning media in the science subject for sixth grade students of Madrasah Ibtidaiyah Negeri 3 Jember by using ADDIE Model. This study used data collection instruments such as observation, interviews, questionnaires, documentation and tests with descriptive qualitative and quantitative data analysis techniques. The results of the study show: 1) the product developed is the ZATASE media for the subject of science for sixth grade students of Madrasah Ibtidaiyah Negeri 3 Jember, 2) the percentage results of the five validators, namely material experts, media experts, language experts and learning experts are 93.74% which means "very feasible", 3) the results of the effectiveness test using the t-test with Paired Sample T-test obtained a sig value (2-tailed) of 0.000 <0.05 which means there is a difference between before and after using the ZATASE media. The N-Gain test obtained a score of 0.69, meaning it has a moderate increase. Thus, it can be concluded that the ZATASE learning media is "quite effective" when applied in science subject learning.